(3OGYi GdadGMs ((3GdeLeY GdbjJHGYi (B_ (3ecI s)
(3ChdgG (B:s
(3dge hGdaGA ddZJge deNGdWI ZjQ GdLfS s
(3BNQgG (B:s
(3hgPG GdMce eSJfHW ef CUhdgG OdI Gdabg Je HMeO Gddg hYhfg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdESdGejs